2019
DOI: 10.1088/1758-5090/ab4cca
|View full text |Cite
|
Sign up to set email alerts
|

Fast three-dimensional micropatterning of PC12 cells in rapidly crosslinked hydrogel scaffolds using ultrasonic standing waves

Abstract: The ability to spatially organise the microenvironment of tissue scaffolds unlocks the potential of many scaffold-based tissue engineering applications. An example application is to aid the regeneration process of peripheral nerve injuries. Herein, we present a promising approach for three-dimensional (3D) micropatterning of nerve cells in tissue scaffolds for peripheral nerve repair. In particular, we demonstrate the 3D micropatterning of PC12 cells in a gelatin-hydroxyphenylpropionic acid (Gtn-HPA) hydrogel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 66 publications
0
20
0
Order By: Relevance
“…Additionaly, the MPAFC system enalbes us accurately distinguish the melanoma cell in pure blood, and has a high detection sensitivity of 100 cells mL –1 . For future studies, we can further boost the throughput of this technique by using a higher frequency laser with more exciting wavelengths via the stimulated Raman scattering (SRS) effect to observe cells with a higher flow rate and richer cellular information, , increasing the center frequency of ASW to form more focusing nodes in a single channel, utilizing the interdigital transducers to exit higher energy ultrasound waves. , Designing multichannel chip coupled with a region-of-interest scanning mechanism, and integrating microring resonator (MRR) to provide an isotropic spatial resolution. In summary, MPAFC realizes high-resolution imaging, high-accuracy recognition, high sensitivity detection, and high-efficiency elimination of moving cells in the channel filled with strong optical scattering media and has great potential for both fundamental and clinical applications.…”
Section: Discussionmentioning
confidence: 99%
“…Additionaly, the MPAFC system enalbes us accurately distinguish the melanoma cell in pure blood, and has a high detection sensitivity of 100 cells mL –1 . For future studies, we can further boost the throughput of this technique by using a higher frequency laser with more exciting wavelengths via the stimulated Raman scattering (SRS) effect to observe cells with a higher flow rate and richer cellular information, , increasing the center frequency of ASW to form more focusing nodes in a single channel, utilizing the interdigital transducers to exit higher energy ultrasound waves. , Designing multichannel chip coupled with a region-of-interest scanning mechanism, and integrating microring resonator (MRR) to provide an isotropic spatial resolution. In summary, MPAFC realizes high-resolution imaging, high-accuracy recognition, high sensitivity detection, and high-efficiency elimination of moving cells in the channel filled with strong optical scattering media and has great potential for both fundamental and clinical applications.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 Also, phased-array emitters around a liquidfilled chamber 19 or diffractive beam shaping, 20 are employed, for instance for cell-sorting, 21 or patterning in ultrasonic gels. 22 Taking holographic optical tweezers (HOT) as a model, holographic acoustic tweezers (HAT) enable control of individual particles levitated in water 23 or air. 24 For the relatively large samples considered here, it is advantageous to use a simpler approach based on bulk acoustic waves rather than surface acoustic waves, since larger specimen size requires larger chamber volumes.…”
Section: Introductionmentioning
confidence: 99%
“…Kurashina et al have reported a technique for cultivating adhesive cells using ultrasound vibration 23 and showed that the resonant flexural vibration of the cell culture surface combined with chemical treatment improved the cultivation efficiency of the cells. Cheng et al reported the patterning of neural cells in hydrogel scaffolds using a three-dimensional ultrasonic standing wave 24 , showing the direction of neurites can be aligned along the nodal plane.…”
Section: Introductionmentioning
confidence: 99%